2003
DOI: 10.1074/jbc.m209200200
|View full text |Cite
|
Sign up to set email alerts
|

Absence of p21CIP Rescues Myogenic Progenitor Cell Proliferative and Regenerative Capacity in Foxk1 Null Mice

Abstract: Foxk1 is a forkhead/winged helix transcription factor that is restricted to myogenic progenitor cells in adult skeletal muscle. Mice lacking Foxk1 (Foxk1؊/؊) display growth retardation and a severe impairment in skeletal muscle regeneration following injury. Here we show that myogenic progenitor cells from Foxk1؊/؊ mice are reduced in number and have perturbed cell cycle progression (G 0 /G 1 arrest). Molecular analysis of Foxk1؊/؊ myogenic progenitor cells revealed increased expression of the cyclin-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 35 publications
4
92
0
1
Order By: Relevance
“…7C). These results are consistent with previous reports that demonstrated FOXK1-mediated repression of p21 gene expression and increased proliferation in the C2C12 myoblast cell line (45). Furthermore, we performed immunoblotting of cell lysates derived from asynchronous and mitotic cells expressing control Protein lysates from these cells were immunoblotted (IB) using the indicated antisera.…”
Section: Protein Namessupporting
confidence: 91%
See 1 more Smart Citation
“…7C). These results are consistent with previous reports that demonstrated FOXK1-mediated repression of p21 gene expression and increased proliferation in the C2C12 myoblast cell line (45). Furthermore, we performed immunoblotting of cell lysates derived from asynchronous and mitotic cells expressing control Protein lysates from these cells were immunoblotted (IB) using the indicated antisera.…”
Section: Protein Namessupporting
confidence: 91%
“…PLK1 has been shown to phosphorylate and regulate the localization and transcriptional function of various FOX transcription factors, FOXM1 (39), FOXO1 (40), and FOXO3 (41). Although FOXK1 is implicated as a regulator of myogenic proliferation (21,(43)(44)(45), little is known about its function during mitosis. Previous studies have shown that CYCLIN-CDK complexes phosphorylate FOXK2, a protein that is highly homologous to FOXK1, during mitosis and that such phosphorylation regulates its stability and transcriptional function (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted here that Sp1 is not the only transcription factor believed to recognize the CCAC-box motif. Data by the Williams laboratory suggest that the myocyte nuclear factor (MNF), a member of the winged-helix family of transcription factors, also recognizes this DNA-binding motif and serves a role in myogenesis and muscle regeneration (Bassel-Duby et al, 1994;Garry et al, 2000;Garry et al, 1997;Hawke et al, 2003;Meeson et al, 2007;Shi et al, 2010;Yang et al, 1997;Yang et al, 2000). However, to date there are no detailed studies investigating the role of MNF in modulating myoglobin transcriptional activity.…”
Section: Network Of Regulatory Motifs Within the Myoglobin Promotermentioning
confidence: 99%
“…-/- (Hawke et al, 2003), Pop1 -/- (Andrée et al, 2002) and Slug -/- mice. Similarly, we report here that specific deletion of Cx43 delays regeneration by >7 days.…”
Section: Expression Of Connexins In Resting and Regenerating Tasmentioning
confidence: 99%